Scarcity, government, population: The problem of food in colonial Kenya, c. 1900-1952 - Duminy, James (School of Architecture, Planning and Geomatics, 2018)
Food security in Africa is a foremost development challenge. Dominant approaches to addressing food security concentrate on availability and increasing production. This 'productionist' focus arguably limits the capacity of government policies to address contemporary food problems. It does so by obscuring both the specific food insecurity dynamics linked to the continent's ongoing urban transitions, as well as the potential for more systemic food strategies. Yet existing research provides an inadequate historical understanding of how a production and supply-oriented bias has emerged and become established in the African context. This undermines the capacity of scholars and policymakers to critique and reform food security thought and practice. The thesis addresses this gap in knowledge by critically and historically examining the emergence of food scarcity as a specific problem of government in a particular African context: colonial Kenya. Understanding how colonial officials and other actors conceived of and responded to food scarcities in Kenya is the primary question addressed. The specific roles and duties of the state in relation to this problem are also investigated. The thesis employs a Foucauldian-inspired approach to the historical analysis of government and problematizations. Primary data were gathered from archives in the United Kingdom. The argument is that food scarcity, as a problem of government, shifted from an uncertain and localized rural issue to a risk encompassing the balance between market supply and demand at a territorial scale. The role of the state shifted from a last-resort provider of relief to a regulator of maize production and demand, with a focus on ensuring adequate supply for territorial self-sufficiency. Accordingly, anti-scarcity techniques became increasingly economic and calculative in nature, and longer term in focus. This mode of conceiving and addressing food scarcity existed in Kenya by the end of the Second World War, and was stabilized in the immediate post-war period. Elements of this system are recognizable in contemporary food security policies in Kenya and elsewhere in Africa. The thesis contributes to historical knowledge of African food insecurity and colonial government. It moves beyond previous work by focusing on Kenya, and by examining food scarcity as a distinct problem of colonial government. It enhances knowledge of the conditions under which contemporary modes of food governance have come into existence.